Impact of five SNPs in dopamine‐related genes on executive function. (25th April 2012) - Mitaki, S.; Isomura, M.; Maniwa, K.; Yamasaki, M.; Nagai, A.; Nabika, T.; Yamaguchi, S.
<x xml:space="preserve">Abstract</x> Objectives Dopamine neurotransmission is a critical factor for executive function, which is controlled by the prefrontal cortex in humans. Although the contribution of genetic factors to the regulation of brain dopaminergic activity is widely acknowledged, identification of a genotype–phenotype association has not yet been clearly established. In this study, we therefore evaluated the effects of five functional single‐nucleotide polymorphisms (SNPs) in specific genes related to dopamine neurotransmission on executive function in a general population. Materials and methods Participants of the health examination at the Shimane Institute of Health Science were recruited for this study (n = 964). To evaluate executive function, the Frontal Assessment Battery (FAB) was administered. SNPs were genotyped using the TaqMan method. Results A significant association was found between an SNP in the catechol‐O‐methyltransferase (COMT) gene (rs4680) encoding the low‐activity Met allele and FAB score (P = 0.003). Of note, the flexibility subset of the FAB was associated with the SNP in COMT (P = 0.003) after adjustment for confounding factors. The generalized multifactor dimensionality reduction method identified that the combination of two SNPs in the COMT gene (rs4680) and the dopamine D4 receptor gene (rs1800955) had a significant effect on FAB score. Conclusions Our study indicates a contribution of rs4680 in the COMT gene to the variability in executive function, as assessed by the FAB. In addition, we have indicated that a complex gene–gene interaction between SNPs in the genes related to dopamine neurotransmission may influence executive function in a general population.